Measuring 8 to 12 year old children's self-report of power imbalance in relation to bullying: Development of the Scale of Perceived Power Imbalance - Nelson, Helen; Kendall, Garth; Burns, Sharyn; Schonert-Reichl, K.A.; Kane, Robert (BMC, 2019)
Background: While power imbalance is now recognized as a key component of bullying, reliable and valid measurement instruments have yet to be developed. This research aimed to develop a self-report instrument that measures power imbalance as perceived by the victim of frequent aggressive behavior.